Swarm Networks in Brownian Environments - Mori, Masashi; Isokawa, Teijiro; Peper, Ferdinand; Matsui, Nobuyuki (New generation computing, 2015)
Swarm Networks are a generalization of Cellular Automata, in which the neighborhoods and functionalities of cells are determined by the presence or absence of connections between cells. This paper presents a Swarm Network in which connections can be changed dynamically, and in which the cells (called “agents”) are subject to Brownian motion. According to these characteristics, the model mimics behavior typically encountered in biological organisms. We show that this model is capable of universal computation by constructing a universal Brownian circuit based on it.